Strategies for Well-Being in Interventional Radiology. Issue 1 (February 2023) - Farooq, Amina; Hamilton, Barbara
Interventional radiologists (IRs) have a massive impact on their patients, communities, and healthcare at large. Yet, IRs have physical and emotional challenges that lead to a high rate of burnout compared with other medical specialties. A Medscape survey in 2013 showed a 37% burnout incidence among radiologists, which increased to 49% in 2015. This ranked radiology 7th out of 26 specialties with respect to burnout. Although the survey did not examine IR specifically, with the increasing demands on those in the profession, this number can only be expected to increase. A survey by Bundy et al demonstrated that interventional radiologists are in the upper range of burnout among physicians with 71.9% presenting with at least 1 manifestation of burnout. This is higher than that reported among surgeons or diagnostic radiologists. We must be proactive in addressing wellness in IR if we are to flourish both individually and as a group. The impact of suboptimal well-being in an IR goes beyond that of the individual, influencing patient care with ripple effects to society at large. At worst, severe burnout can lead to an early exit from medicine, with the cost of recruiting a replacement IR estimated at two to three times an annual physician salary. This is to say nothing of the experience, wisdom, and leadership that are lost when physicians burn out and drop out. Particularly in IR, where the work performed often improves the cost-effectiveness and quality of care, burnout is a threat to the physician workforce and healthcare at large. In this article, our goal is to share some elements of physician well-being and highlight opportunities to support well-being in IR.